PERAN UNIT PPA DALAM MENERAPKAN TEORI RESTORATIVE JUSTICE PADA TINDAK PIDANA PENCURIAN TERHADAP PELAKU ANAK DI KOTA GORONTALO - Nopiana Mozin; Yasmirah Mandasari Saragih (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2021)
This study aims to find out and analyze how the role of the women’s and children’s service units in the application of the principle of restorative justice in criminal acts of children as perpetrators and what factors are obstacles to women’s and children’s service units in the application of the principle of restorative justice in criminal acts of children as this research is empirical to achieve this goal the authors use data collection techniques in the form of unterviews and ask for data from the women’s and children’s services Unit in Gorontalo City Police The Results of the study show that the role of the PPA unit is to carry out a mediation process in accordance with the custom of deliberation. In applaying the principle of Restorative Justice in Gorontalo City carried out by the police that is done through activities such as mediation of victims with perpetratos/violators,and family group deliberations, which are of a recovery nature for both victims and perpetrators. Factors which become obstacles for the Womens and Children’s Services Unit in applying the principle of restorative justice in child crime as a perpetrator,namely when inviting the victimand his family which at that time were still not received with the existence of a criminal offense committed by the pretrator as well as finding the address of the victim and suspects where if providing incomplete address, making it difficult for the police in solving problems that occur between victims and perpetrators